FAKTOR EKSTERNAL YANG MEMPENGARUHI RENDAHNYA HASIL BELAJAR GEOGRAFI SISWA KELAS XI IPS SMA NEGERI I TALAMAU KABUPATEN PASAMAN BARAT - Yenni, Marvia Elvi; Ahmad, Ridwan; Erita, Yenni (Pendidikan Geografi, 2013)
The purposes of this research to know the factor influence about studentâs low study of geography class XI IPS SMA N Talamau Kabupaten Pasaman Barat. According to phenomenon were environment habitation, physic of school environment, and the influence of tool and infrastructure based on the result study of geography.The kinds of this research were descriptive correlation as the research approachÂ Â  with manufactory data to used statistic analysis, the variable classification research was into free variable and string variable.Â  The population and sample of this research, the population was student of class XI IPS SMA N Talamau Kabupaten Pasaman Barat with the totalâs students 79, whereas the sample of this research from population used to technique total sampling, it purposes to easier in process collecting data with method all population as a sample.The result of this research, the researcher found that 1) the distance habitation based on the result studentâs study geography in class XI IPS SMA N Talamau Kabupaten Pasaman Barat, 2) the influence based on significant between physical environments of school on the result studentsâ study of geography in class XI IPS SMA N Talamau Kabupaten Pasaman Barat, 3) the influence based on significant between tool and infrastructure on the result studentsâ study of geography in class XI IPS SMA N Talamau Kabupaten Pasaman Barat, and 4) the influence based on distance habitation, physical environment of school, and tool and infrastructure based on the result studentsâ study of geography in class XI IPS SMA N Talamau Kabupaten Pasaman Barat